Fire hydrants : installation, field testing, and maintenance of fire hydrants. (American Water Works Association, 2016)
A thorough discussion of wet-barrel and dry-barrel hydrants, including installation and testing.
"Manual of water supply practices"--Cover.
" ... prepared by the AWWA Standards Committee on Fire Hydrants"--Foreword.
"1P-4C-30017-5E (5/16) IW"--Page 4 of cover.
Keywords: Hydrants.; elektronické knihy; electronic books